Reliability and Reproducibility of Neuromelanin‐Sensitive Imaging of the Substantia Nigra: A Comparison of Three Different Sequences. Issue 3 (9th October 2020) - van der Pluijm, Marieke; Cassidy, Clifford; Zandstra, Melissa; Wallert, Elon; de Bruin, Kora; Booij, Jan; de Haan, Lieuwe; Horga, Guillermo; van de Giessen, Elsmarieke
Abstract : Background: Neuromelanin‐sensitive MRI (NM‐MRI) of the substantia nigra provides a noninvasive way to acquire an indirect measure of dopamine functioning. Despite the potential of NM‐MRI as a candidate biomarker for dopaminergic pathology, studies about its reproducibility are sparse. Purpose: To assess the test–retest reproducibility of three commonly used NM‐MRI sequences and evaluate three analysis methods. Study Type: Prospective study. Population: A total of 11 healthy participants age between 20–27 years. Field Strength/Sequence: 3.0T; NM‐MRI gradient recalled echo (GRE) with magnetization transfer (MT) pulse; NM‐MRI turbo spin echo (TSE) with MT pulse; NM‐MRI TSE without MT pulse. Assessment: Participants were scanned twice with a 3‐week interval. Manual analysis, threshold analysis, and voxelwise analysis were performed for volume and contrast ratio (CR) measurements. Statistical Tests: Intraclass correlation coefficients (ICCs) were calculated for test–retest and inter‐ and intrarater variability. Results: The GRE sequence achieved the highest contrast and lowest variability (4.9–5.7%) and showed substantial to almost perfect test–retest ICC (0.72–0.90) for CR measurements. For volume measurements, the manual analysis showed a higher variability (10.7–17.9%) and scored lower test–retest ICCs (–0.13–0.73) than the other analysis methods. The threshold analysis showed higher test–retest ICC (0.77) than the manual analysis for the volume measurements. Data Conclusion: NM‐MRI is a highly reproducible measure, especially when using the GRE sequence and CR measurements. Volume measurements appear to be more sensitive to inter/intrarater variability and variability in placement and orientation of the NM‐MRI slab. The threshold analysis appears to be the best alternative for volume analysis. Level of Evidence: 2 Technical Efficacy Stage: 1